CONDUCTIMETRIC TITRATION OF DICARBOXYLIC-ACIDS IN 1-PROPANOL - BOZDOGAN, A; OZEROGLU, C; KUNT, G; SARAC, S (EDITURA ACADEMIEI ROMANE, 1993)
The conductimetric titrations of aliphatic and aromatic dicarboxylic acids have been investigated for the solvent 1-propanol. Good analitical results were obtained by using tetrabutylammonium hydroxide as titrant. Conductimetric titration curves and results were presented and compared to that obtained from titration of dicarboxylic acids in non-aqueous solvents. Two well-resolved end points were observed at 1 : 1 and 1 : 2 acid/base stoichiometry. The end points were determined by using the confidence interval of end points defined by the intersection of straight lines.
Keywords: CONDUCTOMETRIC TITRATIONS; 2-METHOXYETHANOL; SOLVENTS; Chemistry